Ageing, cellular senescence and the impact of diet: an overview. Issue 1 (11th January 2021) - Maduro, Ana T.; Luís, Carla; Soares, Raquel
Abstract : Abstract: Ageing is a risk factor for chronic diseases including cancer, cardiovascular diseases, neurodegenerative disorders, and metabolic syndrome. Among others, senescence mechanisms have become a target of huge research on the topic of the ageing process. Cellular senescence is a state of an irreversible growth arrest that occurs in response to various forms of cellular stress and is characterized by a pro-inflammatory secretory phenotype. Multiple studies showed that cellular senescence occurs in both physiological and pathophysiological conditions. Senescent cells accumulate with ageing and can contribute to age-related decline in tissue function. Obesity is a metabolic condition that can accelerate the ageing process by promoting a premature induction of the senescent state of the cells. In contrast, caloric restriction without malnutrition is currently the most effective non-genetic intervention to delay ageing, and its potential in decreasing the cellular senescent burden is suggested. Here, it will be highlighted the cellular and molecular mechanisms involved in cellular senescence and discussed some of the research that is being done about how environmental conditions such as diet can affect the accumulation of senescent cells.